BALANCING INVESTOR PROTECTION AND SUSTAINABLE DEVELOPMENT IN INVESTMENT ARBITRATION: Abdurakhmonova Noila - LLM in International arbitration; dispute settlement Tashkent State University of Law, Abdurakhmonova Noila (Лучшие интеллектуальные исследования, 2024)
Investment arbitration was originally developed primarily to protect investors from wealthy developed countries against arbitrary expropriations by governments in developing countries. However, over time, it has taken on a very broad dynamic and is nowadays often used to limit regulatory interference of any government with the business plans of any foreign or foreign owned companies. This is causing "regulatory chill" in many parts of the world, where governments, in particular in less developed or less affluent countries, are weary of changing or enforcing environmental protections, labor laws, consumer laws, etc., because they have already been forced to pay after costly arbitration proceedings in similar cases. We cite a number of examples where countries were trying to introduce sensible regulation in response to changing circumstances and ended up paying damages to investors who might never have been able to implement their business ideas even in the absence of the regulatory changes. As a result, we not only see an undue limitation on the sovereignty of many countries and governments and their ability to regulate in the best interest of their citizens. We also see more and more countries turning their backs on investor-state arbitration and on bilateral or multilateral protection treaties in general. A complete breakdown of the established system may not be imminent but talk about a crisis does no longer seem alarmist. What is needed, therefore, is a re-balancing of the rights and obligations of the investors and the host countries, and a better appreciation of sustainable development goals and other valid public interest considerations in the host countries. This idea is not new and we are not the first ones to postulate the need for change. However, we may be offering some new ideas and a new evaluation of some existing ideas on how such a change could be brought about in practice.